1978
DOI: 10.1111/j.1151-2916.1978.tb09344.x
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Phases in Hot‐Pressed Si3N4

Abstract: Impurity phases in commercial hot-pressed Si,,N4 were investigated using transmission electron microscopy. In addition to the dominant ,B-Si:,N, phase, small amounts of Si2N,0, Sic, and WC were found. Significantly, a continuous grain-boundary phase was observed in the -25 high-angle boundaries examined. This film is = 10 b thick between ,B-Si:,N, grains and -30 b thick between Si2N,0 and P-Si:,N, grains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…If the liquid width is small, on the order of a few atomic diameters, then small grain dissolution and precipitation on the large grains is controlling [34,149,150]. For systems where the liquid film thickness is on the order of 1-3 lm, contact flattening dominates densification.…”
Section: Densificationmentioning
confidence: 99%
“…If the liquid width is small, on the order of a few atomic diameters, then small grain dissolution and precipitation on the large grains is controlling [34,149,150]. For systems where the liquid film thickness is on the order of 1-3 lm, contact flattening dominates densification.…”
Section: Densificationmentioning
confidence: 99%
“…Many studies have since reported on the effects of these grain boundary structures on the overall physical and mechanical properties in metals and ceramics, such as the being cause for solid state activated sintering and abnormal grain growth. [29][30][31][32][33][34][35][36][37] Recently, Tang et al 38 introduced the term complexion to differentiate grain boundary "phases" from traditional bulk phases. The main reason for this convention is that complexions depend on their abutting grains and cannot exist as separate entities.…”
Section: Introductionmentioning
confidence: 99%
“…Three groups of additives have been used [1, [5][6][7]: (a) oxides (MgO, ^2 Q 3> ^2°3 * Al2°3) > which do not form solid solutions with 813114; (b) oxide and non-oxide additives (BeO, BeSiN2, Al2C>3 + A1N, A1N + Y2°3) which do form solid solutions with Si3N4; and (c) non-oxide additives (863^, ZrN, ZrC, Zr + A1N, Mg3N2) which give higher viscosity grain boundary phases. Additives such as MgO result in a continuous, amorphous, magnesium silicate intergranular phase [8][9][10][11], whilst those containing Y203~Al203 additions may possess both crystalline and amorphous grain boundary phases [12][13][14][15]. The presence of a glassy grain boundary phase is deleterious to both the room temperature and elevated temperature mechanical properties of silicon nitride.…”
mentioning
confidence: 99%